2019
DOI: 10.1371/journal.pone.0224266
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein to albumin ratio predicts the outcome in renal cell carcinoma: A meta-analysis

Abstract: BackgroundGrowing evidence has revealed that pretreatment C-reactive protein to albumin ratio (CAR) are associated with prognosis for patients with renal cell carcinoma (RCC). However, inconsistent findings have been reported, which promote us to summarize the global predicting role of CAR for survival in RCC patients.MethodsTwo reviewers independently retrieved the literature on EMBASE, MEDLINE, and Cochrane Library databases for eligible studies evaluating the associations of CAR with survival. Data related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…40 In addition, a recent meta-analysis showed that a high pretreatment CAR was associated with worse OS and DFS/PFS in patients with renal cell carcinoma (RCC), and a high CAR was also correlated with a variety of clinicopathological features. 41 The pooled results in the present metaanalysis on pancreatic cancer also suggested that an elevated CAR was associated with poor OS, PFS, and DFS, consistent with the findings from other types of cancer. We also found that a high CAR was associated with male sex; that is, male patients with pancreatic cancer tend to have a higher CAR.…”
Section: Discussionsupporting
confidence: 87%
“…40 In addition, a recent meta-analysis showed that a high pretreatment CAR was associated with worse OS and DFS/PFS in patients with renal cell carcinoma (RCC), and a high CAR was also correlated with a variety of clinicopathological features. 41 The pooled results in the present metaanalysis on pancreatic cancer also suggested that an elevated CAR was associated with poor OS, PFS, and DFS, consistent with the findings from other types of cancer. We also found that a high CAR was associated with male sex; that is, male patients with pancreatic cancer tend to have a higher CAR.…”
Section: Discussionsupporting
confidence: 87%
“…Another recent meta-analysis suggested that an elevated pretreatment CRP/Alb ratio could independently predict poor OS in patients with pancreatic cancer (33). Zhou et al observed that a high pretreatment CRP/Alb ratio predicted poor survival in patients with renal cell carcinoma (36). In our meta-analysis, the CRP/Alb ratio was correlated with poor OS, PFS, and DFS and also predicted advanced FIGO stages.…”
Section: Discussionsupporting
confidence: 52%
“…At different stages of tumorigenesis, invasion, and metastasis, tumor cells and related inflammatory cells release a large amount of cytokines, chemokines, and other inflammatory factors to promote tumor initiation ( 10 , 36 ). Thus, the systemic inflammatory response is significantly associated with the outcome of patients and related inflammatory indicators, such as the NLR, and this may be used as a biomarker for the prognosis of patients with cancer, and may effectively estimate the prognosis of these patients ( 37 , 38 ). Neutrophils can promote cancer progression by directly acting on tumor cells or indirectly altering the tumor microenvironment ( 39 ).…”
Section: Discussionmentioning
confidence: 99%